Lonely individuals reveal proximal social avoidance and distal general approach motivation: Evidence from time perception in social and non‐social contexts. - Wu, Chunlin; Guo, Rui; Chen, Youguo; Long, Changquan (British Journal of Psychology, 2026)
Loneliness is a major public health issue, leading to serious physical and mental health problems. Research has shown that trait‐like, chronically lonely individuals exhibit either avoidance or approach behaviour towards social connections. However, how social avoidance and approach motivation co‐occur in trait‐like, chronically lonely individuals remains unclear. We hypothesized that loneliness would first induce social avoidance and then approach motivation, given the inherent negative bias of loneliness and the general process model of threat and defence, which asserts that threat first activates avoidance motivation followed by approach motivation. To test this hypothesis, we used sub‐ and supra‐second time bisection tasks in social and non‐social contexts based on the motivational dimensional model of time perception. The results showed that high‐loneliness (HL) and low‐loneliness (LL) individuals had similar sub‐second time estimates in non‐social contexts. However, HL individuals lengthened time in the sub‐second range in social contexts and shortened time in the supra‐second range compared to LL individuals, regardless of social or non‐social context. These findings suggest that HL individuals exhibit proximal social avoidance and distal general approach as a defence mechanism, which is consistent with the general process model of threat and defence and extends the evolutionary theory of loneliness.